2014
DOI: 10.5993/ajhb.38.6.14
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Secondhand Smoke Exposure of Children Undergoing Surgery

Abstract: Both parents and clinicians are receptive to clinician-delivered interventions to reduce the SHS exposure of children scheduled for elective surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Qualitative research has identified a preference among smoking parents whose children are undergoing surgery for a harm-reduction message over cessation. 16 However, we also know that parents who are able to make their home smoke free, they are subsequently more likely to go on to make a quit attempt. 17 Families who smoke are potentially reachable within the hospital setting.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research has identified a preference among smoking parents whose children are undergoing surgery for a harm-reduction message over cessation. 16 However, we also know that parents who are able to make their home smoke free, they are subsequently more likely to go on to make a quit attempt. 17 Families who smoke are potentially reachable within the hospital setting.…”
Section: Open Accessmentioning
confidence: 99%
“… 18 There is an expectation among parents in paediatric hospital settings that the physicians will enquire about their smoking, and report that it is acceptable to do this. 16 19 Parents who access care for their child in paediatric emergency departments (EDs) are reported to be motivated to quit and receptive to smoking cessation advice. 20–23 However, less is known about whether parents, if they are not willing or able to quit smoking, are receptive to SHS harm reduction advice in this setting, although there is qualitative evidence to suggest that the health of the child is as a motivating factor among parents to change their smoking behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…The minimal time required for recovery of organ dysfunction after smoking cessation for wound healing is 3 to 4 weeks, 7 for bone healing is 4 weeks, 8 for immune competence is 2 to 6 weeks and for pulmonary function is 6 to 8 weeks. 9 For planned admissions, smoking cessation 8 weeks or more before admission is considered by National Health Service, UK as an optimum amount of time for the body to recover from the immediate effects of smoking. 10 The deleterious effects of smoking on the musculoskeletal system seem to be partially reversible and quitting smoking before operation mitigates the adverse effects of smoking on postoperative complications.…”
mentioning
confidence: 99%
“…In practice, smoking parents are more ready to accept environmental tobacco smoke exposure mitigation than smoke quitting. 20 Smoking is not allowed in hospital and throughout the perioperative period. The no smoking hospital environment creates an external force to support abstinence.…”
mentioning
confidence: 99%